Westernised Chinese in Yu Hua’s Chronicle of a Blood Merchant - Wang, Aiqing (Language Circle: Journal of Language and Literature, 2022)
Yu Hua is one of the most illustrious avant-garde and post-modernist writers in contemporary China, whose chefs-d’oeuvre can be exemplified by a 1995 novel Chronicle of a Blood Merchant. Notwithstanding widespread accolades, Yu Hua’s fiction is excoriated by his peer Han Han for resembling works translated from Western literature. In this research, I scrutinise the language deployed in Chronicle of a Blood Merchant under the framework postulated by Yu Kwang-chung. I propound that the language in Chronicle of a Blood Merchant bears similitude to Westernised/Europeanised Chinese, in that it involves conspicuous light verbs, nominalisation, bei passivisation, subordinating and coordinating conjunctions, plural forms, as well as premodifiers and particles, a considerable proportion of which are redundant and impinged upon by the English language.